KONTRIBUSI KUALITAS LAYANAN, BAURAN PEMASARAN DAN CUSTOMER VALUE DALAM MENCIPTAKAN KEPUASAN NASABAH PT BANK SYARIAH INDONESIA Tbk KANTOR CABANG MADIUN - Fortunella Fistha Permadani; Audita Nuvriasari (MANAJEMEN DEWANTARA, 2023)
The development of the Islamic banking industry encourages service providers to be oriented towards creating customer satisfaction. The purpose of this study was to analyze the effect of service quality, marketing mix and customer value on customer satisfaction of PT Bank Syariah Indonesia Tbk Madiun Branch Office. The sampling technique uses purposive sampling with a total sample of 100 customers. Research respondents are customers who use banking services directly at PT Bank Syariah Indonesia Tbk Madiun Branch Office. The analytical tool used is multiple linear regression analysis. The results of the study prove that: service quality and customer value have a positive and significant effect on customer satisfaction, while the marketing mix has no significant effect on customer satisfaction.